Is the Unequal Treatment of Debtors in Natural Person Insolvency Law Justifiable?: A South African Exposition. Issue 1 (18th January 2016) - Coetzee, Hermie
Abstract: The South African natural person insolvency system has remained largely creditor‐orientated and excludes many honest but unfortunate debtors from its ambit. This is despite the worldwide trend to accommodate all such debtors. Although the system does provide for three different statutory natural person debt relief procedures, the cumulative effect of these measures' entry requirements results in differentiation on financial grounds. This is as all statutory measures require the debtor to have some form of disposable assets or income available – thereby drawing a distinction between those debtors with and those without assets and or income (the so‐called no income no asset debtors). The main aim of this article is to measure the South African natural person insolvency system against the right to equality in terms of both the South African Constitution and the Promotion of Equality and Prevention of Unfair Discrimination Act. The article may benefit legislatures and policymakers in constitutional jurisdictions that subscribe to the equality principle and that directly or indirectly exclude some debtors from debt relief while providing others therewith. Copyright © 2016 INSOL International and John Wiley & Sons, Ltd.